2019
DOI: 10.5194/bg-16-4731-2019
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen use efficiency and N<sub>2</sub>O and NH<sub>3</sub> losses attributed to three fertiliser types applied to an intensively managed silage crop

Abstract: Abstract. Three different nitrogen (N) fertiliser types, ammonium nitrate, urea and urea coated with a urease inhibitor (Agrotain®), were applied at standard rates (70 kg N ha−1) to experimental plots in a typical and intensively managed grassland area at the Easter Bush Farm Estate (Scotland). The nitrogen use efficiency of the fertilisers was investigated as well as nitrogen losses in the form of nitrous oxide fluxes (N2O) and ammonia (NH3) during fertilisation events in the 2016 and 2017 growing seasons. Ni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…This suggests that adding Agrotain® to urea may have some beneficial effect reducing emissions of N 2 O and NO. Similarly, Cowan et al (2019) and Smith et al (2012) found that the use of a urease inhibitor in the field can provide some mitigation of N 2 O emission both in UK crop and grasslands, and Kuang et al (2019) reported reduced N 2 O emissions from a laboratory study using a sandy loam from North West China. This was also concluded in a global meta-analysis evaluating a range of enhanced-efficiency fertilizers, including fertilizers with urease inhibitors (Akiyama et al 2010).…”
Section: N Fertilized Agricultural Soilsmentioning
confidence: 93%
See 1 more Smart Citation
“…This suggests that adding Agrotain® to urea may have some beneficial effect reducing emissions of N 2 O and NO. Similarly, Cowan et al (2019) and Smith et al (2012) found that the use of a urease inhibitor in the field can provide some mitigation of N 2 O emission both in UK crop and grasslands, and Kuang et al (2019) reported reduced N 2 O emissions from a laboratory study using a sandy loam from North West China. This was also concluded in a global meta-analysis evaluating a range of enhanced-efficiency fertilizers, including fertilizers with urease inhibitors (Akiyama et al 2010).…”
Section: N Fertilized Agricultural Soilsmentioning
confidence: 93%
“…It is a dry N stabilizer developed by Koch Agronomic Services (2020). A previous study found that the influence of Agrotain® on soil N concentration and N gas emission occurred within approximately two weeks after fertilizer application (Cowan et al 2019).…”
Section: Methodsmentioning
confidence: 98%
“…farm machinery or by hand). The studies report data collected using the flux chamber approach with the exception of a single study which reports data collected using the eddy covariance method (see Cowan et al, 2019b ). The flux chamber method uses an airtight enclosure placed over the soil which allows for gas emissions from the surface to accumulate (typically 30 to 60 min).…”
Section: Methodsmentioning
confidence: 99%
“…Some of the EFs in the published studies are calculated by taking a yearly average after several fertiliser applications, while others report emissions for a shorter period after the event (e.g. Skiba et al, 2013 , Cowan et al, 2019a , Cowan et al, 2019b ). The fluxes derived from the data taken from the AEDA archives report EFs for emissions up to 25 days after fertilisation.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing NUE in fertilisers are associated with a slower release of nutrients by reducing N losses, which is considered to improve yields and mitigate N 2 O emissions [16,17]. Although stabilized fertilisers have been formulated to accomplish high yield and NUE by reducing N losses, many findings showed that the effectiveness of these fertilisers are often influenced by environmental conditions, soil characteristics, and management practices [18][19][20][21][22]. Soil moisture is an important factor affecting the magnitude of N 2 O emissions from fertilised soil by limiting oxygen concentrations in soil [23] and determining the extent of mineral N accumulations [24].…”
Section: Introductionmentioning
confidence: 99%